Unnatural Sialic Acids for Modulation of Cellular Adhesion and Chimeric Tissue Assembly & Novel Methodologies for Stereocontrolled Deoxy-Sugar Construction - Issa, John. (2017)
Abstract: I. Synthesis and Expression of Fluorinated Sialic Acids for Modulation of Cellular Adhesion We have demonstrated that by supplementing cell growth media for HeLa and BJAB K20 cells with unnatural sialic acids, we are able to modulate the adherent properties of these cell lines. The cells are able to integrate the unnatural sialic acids onto their surfaces through the sialic acid biosynthetic pathway. Specifically, fluorinated sialic acids incorporated onto the cell surface tend to cause diminished adherence of the cells to a hydrophilic glass surface but an increase on tetrafluoroethylene surfaces. We have measured the cell contact angles with the orthogonal surface as a means of quantifying the adhesion, as well as calculated the average sialic acid moieties incorporated per cell. We have also demonstrated the potential reversibility of this adhesion through use of solvents that override the cell-to-surface interaction. II. Halide Effects on Cyclopropenium Cation Promoted Glycosylation with Deoxy Sugars: Highly α-Selective Glycosylations Using a 3,3-Dibromo-1,2-diphenylcyclopropene Promoter A mixture of 3,3-dibromocyclopropene and TBAI promotes highly α-selective glycosylation reactions (up to >20:1) by using deoxy sugar hemiacetal donors. The reaction provides a convenient method for generating highly reactive glycosyl donors in situ from shelf-stable starting materials. Both armed and disarmed sugars undergo the reaction, and selectivity is independent of the absolute configuration of the donor sugar. III. Reagent Controlled β‑Specific Dehydrative Glycosylation Reactions with 2‑Deoxy-Sugars N-Sulfonyl imidazoles activate 2-deoxy-sugar hemiacetals for glycosylation by converting them into glycosyl sulfonates in situ. N-Sulfonyl imidazoles can be synthesized in a trivial fashion and span an enormous range of reactivity. By matching the leaving group ability of the sulfonate with the reactivity of the donor, it is possible to obtain β-specific glycosylation reactions. The reaction serves as proof of the principle that, by choosing promoters that can modulate the reactivity of active intermediates, it is possible to place glycosylation reactions entirely under reagent control. IV. A Reagent-Controlled SN2‑Glycosylation for the Direct Synthesis of β‑Linked 2‑Deoxy-Sugars The efficient and stereoselective construction of glycosidic linkages remains one of the most formidable challenges in organic chemistry. This is especially true in cases such as β-linked deoxy-sugars, where the outcome of the reaction cannot be controlled using the stereochemical information intrinsic to the glycosyl donor. Here we show that p-toluenesulfonic anhydride activates 2-deoxy-sugar hemiacetals in situ as electrophilic species, which react stereoselectively with nucleophilic acceptors to produce only β-anomers. NMR studies confirm that, under these conditions, the hemiacetal is quantitatively converted into an α-glycosyl tosylate, which is presumably the reactive species in the reaction. This approach demonstrates that use of promoters that activate hemiacetals as well-defined intermediates can be used to permit stereoselective glycosylation through an SN2-pathway. V. Cellular LEGOs: Construction of Chimeric Tissues with Emergent Properties Of the nearly 200 human cell types, only a tiny subset has had the opportunity to interact with each other. We propose the creation of hitherto unknown human microtissues using a toolbox of bio-orthogonal binding partners that can link any type of cell to another. Combinatorial scanning of such assemblies ("Cellular LEGOs") will result in chimeric microtissues with emergent properties. These methods will be part of a strategy for the generation and manipulation of biological entities that are spatially, temporally, and functionally defined with precision. The ability to enable and systematically study non-canonical cellular interfaces will result in behaviors that cannot be predicted from our current knowledge of their elementary components alone. These chimeric human tissues may uncover new areas of biomedical science, have significant translational potential, and surprise us with functions that we cannot currently foresee.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Chemistry.; Advisor: Krishna Kumar.; Committee: Charles Mace, David Walt, and Obadiah Plante.; Keywords: Organic chemistry, and Biochemistry.